Syntheses of 3,4- and 1,4-dihydroquinazolines from 2-aminobenzylamine - Díaz, Jimena E.; Ranieri, Silvia; Gruber, Nadia; Orelli, Liliana R. (Beilstein Journal of Organic Chemistry, 2017)
A straightforward strategy for the synthesis of dihydroquinazolines is presented, which allows for the preparation of 3,4- and 1,4-dihydroquinazolines with different substitution patterns from 2-aminobenzylamine (2-ABA) as common precursor. The required functionalization of both amino groups present in 2-ABA was achieved by different routes involving selective N-acylation and cesium carbonate-mediated N-alkylation reactions, avoiding protection/deprotection steps. The heterocycles were efficiently synthesized in short reaction times by microwave-assisted ring closure of the corresponding aminoamides promoted by ethyl polyphosphate (PPE).
Keywords: dihydroquinazolines; microwaves; N-acylations; N-alkylations; PPE